SHARIAH COMPLIANT ELECTRONIC MONEY IN MALAYSIA: KEY CONCERNS AND ITS PERMISSIBILITY - Aseh, Khairi (Archives of Business Research, 2020)
This paper explains the four main concerns on Shariah-Compliant Electronic Money in Malaysia derived from a discussion meeting by The Shariah Advisory Council of Bank Negara Malaysia (hereafter, SAC). This paper also discussed the permissibility of electronic money from the Islamic Shariah perspective. Hence, this paper is useful for any approved issuer that intends to offer Shariah-compliant e-money. Approved issuers are encouraged to educate their users on the essence of the Shariah-compliant e-money product to avoid misunderstanding of the Shariah ruling.